2020
DOI: 10.3906/yer-2001-9
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, risk assessment, and Pb isotopic evidence for sources of heavy metals in stream sediments around the Ulukışla Basin, Niğde, southern Turkey

Abstract: Concentrations of selected elements (Al, Fe, Mn, Mo, As, Cd, Cu, Cr, Ni, Co, Pb, Sb, and Zn) and Pb isotope ratios were determined in 53 sediments from Alihoca, Gümüş, Horoz, and Çakıt streams around the south-central Taurides (Ulukışla Basin), Niğde, which is a known mining province in Turkey. Several pollution and risk assessment indices were used to assess possible heavy metal pollution in the stream sediments and the associated potential ecological risks. Concentrations of As, Cd, Cu, Cr, Ni, Co, Pb, Sb, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In same time, sedimentary rocks also include Pb contents ranging from 10 mg/kg to 20 mg/kg (Lovering, 1969;Cheema et al 2020). Additionaly, the main origin of Pb pollution in sediments is the metal coating, leather whipping, burning coal and fossil fuels, waste pyromania and paint factories (Kushwaha et al, 2018;Ullah et al, 2017;Yousaf et al, 2017;Cheema et al, 2020 (Lermi and Sunkari, 2020) showed that no Pb pollution of the samples and that present Pb originated from aerosol, gasoline and geogenic sources (Fig. 8b).…”
Section: Lead Isotopic Tracing In the Sandstonementioning
confidence: 97%
“…In same time, sedimentary rocks also include Pb contents ranging from 10 mg/kg to 20 mg/kg (Lovering, 1969;Cheema et al 2020). Additionaly, the main origin of Pb pollution in sediments is the metal coating, leather whipping, burning coal and fossil fuels, waste pyromania and paint factories (Kushwaha et al, 2018;Ullah et al, 2017;Yousaf et al, 2017;Cheema et al, 2020 (Lermi and Sunkari, 2020) showed that no Pb pollution of the samples and that present Pb originated from aerosol, gasoline and geogenic sources (Fig. 8b).…”
Section: Lead Isotopic Tracing In the Sandstonementioning
confidence: 97%
“…The main rocks in the area are metamorphic rocks such as marble and schist and volcano-sedimentary rocks like pyroclastics, pillow lavas, andesite, basalt, limestone, dolomite, which are intruded by granitoids in some places (Fig. 1; Clark and Robertson 2002;Alpaslan et al 2006;Lermi and Sunkari 2020). There are abundant ore slags in most parts of the study area due to the ancient mining activities (Fig.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%
“…In terms of the effect of the PTEs on plants, the bioconcentration factor (BCF) also referred to as biological adsorption coefficient (BAC) is widely used to determine the accumulation levels of PTEs from soil to plants ( Kabata-Pendias 2011;Jiang et al 2020;Luo et al 2020;Nganje et al 2020). However, contamination factor (CF), enrichment factor (EF), index of geoaccumulation (Igeo), and soil pollution index (PI) have been effectively used to estimate the extent of soil contamination by PTEs (e.g., Darwish and Pöllmann 2015;Kowalska et al 2018;Dan-Badjo et al 2019;Kabala et al 2020;Lermi and Sunkari 2020;Nganje et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the performance of the FA, the number of measured element variables were reduced from 12 to 10 by selecting only those elements with a communality of extraction higher than 0.5 (50%) or common variances/0.5 (Bern et al, 2019). The use of this approach in this context has been effectively used with similar intents (Jiang et al, 2017;Rasool et al, 2016;Kazapoe and Arhin, 2019;Lermi and Sunkari, 2020). Prior to this, the concentration data were subjected to log transformations after the data normalities for the elements were examined using the onesample Kolmogorov-Smirnov test (the K-S test of normality) and the Shapiro-Wilk tests.…”
Section: Geochemical Data Analysis and Interpretationmentioning
confidence: 99%